Fact-finding surveys on role of flood fighting in present-day Japan and future prospects: case studies of Yodo River and Yamato River - Hirokazu Sato (Discover Water, 2024)
Abstract Flood mitigation efforts (flood fighting), including raising awareness among local residents, have been crucial in Japan to reduce damage during flood events. In this study, interviews were conducted with three flood fighting management bodies on the Yodo and Yamato Rivers, which still have strong flood fighting corps, and field investigations were performed focusing on the actual operation of flood fighting warehouses, which serve as infrastructure bases for flood fighting. Targets included the flood fighting affairs associations on the left and right banks for the Yodo River and that on the right bank for the Yamato River. The survey results showed that with the progress of flood control measures and river improvement, opportunities to conduct actual flood fighting work during floods decreased in all cases in recent years, but flood fighting techniques and knowledge were passed on through exercises and drills. In addition, the flood fighting warehouses were well managed and maintained their functions as material and equipment storage places and as waiting and meeting places for flood fighting corps members. Considering the intensification of external flood forces due to future extreme weather changes, it was deemed that the role of the flood fighting corps is expected to increase in importance, and it was judged that preparations were being made to respond to this trend. On the other hand, there were some challenges in terms of securing a sufficient number of members due to the shortage resulting from the aging of the corps members and maintaining warehouses from a budgetary standpoint.